Tradire il ‘traditum’. Alcune note a partire da “tecnica e metafisica” di Eugenio Mazzarella - Venezia, Simona (Mechane, 2022)
The paper aims at discussing some conceptual themes of Tecnica e metafisica (Technique and Metaphysics), written by Eugenio Mazzarella in the early 1980s and recently republished. This book represents a landmark for Heideggerian studies even because it proposed an innovative lecture based on the need to highlight the “onticity of the ontology” and the anthropological matrix of Heidegger’s thought. These issues are also discussed by taking into consideration the recent books and developments of Mazzarella’s path.